Tingkat Pengetahuan Ibu yang Memiliki Anak Balita Tentang Stunting di Wilayah Kerja Puskesmas Pahandut Kota Palangka Raya Tahun 2019 - Etri Prillia; Eriani Eriani (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2020)
Stunting (short children) is one of the nutritional problems faced by the world, especially in poor and developing countries, stunting is a health problem because it is related to the risk of illness and death. The purpose of this research was to determine the level of knowledge of mothers who have children under five about stunting in the Pahandut Health Center, Palangka Raya City. This study used a descriptive design with a population of all mothers who had children under five. The sample was taken using the accidental sampling technique so that 30 samples of mothers who had children under five were obtained in the Pahandut Health Center, Palangka Raya City. This study used a questionnaire about maternal knowledge about stunting, data analysis was tabulated using excel, the data obtained were displayed in the form of a pie chart and narrative. The results showed that the level of knowledge of mothers who had children under five about stunting was mostly in the low category. The mother's insufficient knowledge can be caused by: age, education, occupation, number of children, whether or not she received information, and the source of the information. It can be concluded that most of them have less knowledge. So that health workers are expected to increase maternal knowledge about stunting by providing counseling and health education.